Histological study of the gametogenic cycle of the angelwing clam pholas orientalis (GMELIN. 1790) in Kalibo, Aklan, Philippines. - Sobrevega, Saturnino Luke (2013.)
The annual gametogenic cycle of angelwing clam Pholas orientalis (Gmelin, 1790) was studied by histological analysis of the gonads of individuals collected in Kalibo, Aklan, Philippines on the period January 2009 up to February 2010. Spawning occurs in April and ends on November. Gonad development was observed in angelwing clam in September to June. Angelwing clams were observed to be ready to spawn on the months of Novemebr to August. It appeared that gonad development and spawning is almost whole year round in the angelwing clam samples collected in Kalibo, Aklan. Follicular size was used as additional criteria in determining the gonadal stage of angelwing clam.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Angelwing Clams -- Kalibo, Aklan